1999
DOI: 10.1046/j.1365-3059.1999.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Plum pox virus detection in dormant plum trees by PCR and ELISA

Abstract: An immunocapture polymerase chain reaction (IC-PCR) protocol and ELISA were compared for their effectiveness in detecting plum pox virus (PPV) in dormant plum material. Although the IC-PCR was about one thousand times more sensitive than ELISA, PPV was detected by ELISA in 71-80% of bark samples collected in December, January and March 1996/97 from pot-grown rootstock trees inoculated with PPV the previous March, compared with 85-86% detection in the same samples by IC-PCR. In similar samples from one-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Also, reliable and sensitive detection assays are required for effective plant sanitation. Although ELISA is routinely used to detect plant viruses (Adams et al 1999;Valero et al 2003), it is not sensitive enough to detect plant viruses at very low concentrations in plant tissues. To overcome this problem, RT-PCR has been used for virus detection (Manganaris et al 2003;Sharma et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, reliable and sensitive detection assays are required for effective plant sanitation. Although ELISA is routinely used to detect plant viruses (Adams et al 1999;Valero et al 2003), it is not sensitive enough to detect plant viruses at very low concentrations in plant tissues. To overcome this problem, RT-PCR has been used for virus detection (Manganaris et al 2003;Sharma et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…DAS-ELISA is routinely used for the detection of fruit-tree viruses such as PPV (Adams 1978;Adams et al 1999) and PNRSV (Scott et al 1989;Pusey and Yadava 1991). Production of virus-free propagation material by meristem-tip culture requires the use of highly specific, sensitive and rapid detection methods to screen the resulting explants.…”
Section: Virus Detectionmentioning
confidence: 99%
“…However, ELISA lacks the sensitivity required for the detection of these viruses, which occur in low concentration in these tissues. In an attempt to overcome this problem RT-PCR using immunocaptured viral particles (IC-RT-PCR) or total RNA as input and nested RT-PCR have been used for detection of PPV (Wetzel et al 1991;Candresse et al 1995;Adams et al 1999) and PNRSV (Spiegel et al 1996;Rosner et al 1998;Helguera et al 2001). Furthermore, methods based on RNA hybridization using radioactive (Varveri et al 1988;Crosslin et al 1992) and non-radioactive (Heuss-La Rosa et al 1995;Heuss et al 1999) cRNA probes have been employed for their detection.…”
Section: Virus Detectionmentioning
confidence: 99%
“…The latter were also ELISA-negative whereas the parent plant was ELISA-positive. Enzymelinked immunosorbent assay is routinely used for the detection of plant viruses (Adams et al 1999;Robert et al 1998;Valero et al 2003). It was demonstrated that ELISA lacks the sensitivity required for detection of the viruses, which occur in low concentrations in plant tissues.…”
Section: Resultsmentioning
confidence: 99%